RISE IN COSMETIC SURGERY AMONG TEENAGERS - Qoraboyeva Dilnoza Xursanali’s daughter (TADQIQOTLAR, 2026)
Abstract. This article explores the growing trend of cosmetic surgery among teenagers and examines the factors influencing this increase. In recent years, cosmetic procedures have become more accessible and socially acceptable, especially among young people. Through analysis of existing research, surveys, and student perspectives, this study investigates how social media, peer pressure, and changing beauty standards shape teenagers’ attitudes toward cosmetic surgery. The findings suggest that while some teenagers seek procedures for medical or reconstructive reasons, many are influenced by unrealistic beauty ideals and online comparisons. The study also highlights psychological and social implications, including issues related to self- esteem, identity formation, and mental health.